2006
DOI: 10.1097/01.sla.0000237648.90600.e9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nonviral Factors on Hepatitis C Recurrence After Liver Transplantation

Abstract: We have identified donor and recipient characteristics that significantly predict hepatitis C recurrence following liver transplantation. These factors are identifiable before transplant and, if considered when matching donors to HCV recipients, may decrease the incidence of HCV recurrence after OLT. A change in the current national liver allocation system would be needed to realize the full value of this benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 44 publications
5
34
2
Order By: Relevance
“…It was found that there was no significant correlation between donor age and recurrence in the present study, similarly, in the studies by Yosry et al in 2009 [2] and Doris et al in 2010 [11] there were no correlation between donor age and HCV recurrence, In contrast, in the studies by (Berenguer, 2003 [14], Charlton and Menon, 2005 [5], Cameron et al [12], and Francisco et al [10] donor age <31 years was significant predictor of HCV recurrence, perhaps because older grafts are less able to mount an effective immune response against viral recurrence [12].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…It was found that there was no significant correlation between donor age and recurrence in the present study, similarly, in the studies by Yosry et al in 2009 [2] and Doris et al in 2010 [11] there were no correlation between donor age and HCV recurrence, In contrast, in the studies by (Berenguer, 2003 [14], Charlton and Menon, 2005 [5], Cameron et al [12], and Francisco et al [10] donor age <31 years was significant predictor of HCV recurrence, perhaps because older grafts are less able to mount an effective immune response against viral recurrence [12].…”
Section: Discussioncontrasting
confidence: 56%
“…Similarly, in the study by Yosry et al in 2009 [2], and Doris et al [11], there was no correlation between recipient age and HCV recurrence. In contrast, in a study by Charlton [5], older recepients, were significantly correlated with more severe recurrence of HCV, perhaps because older patients are less able to mount an effective immune response against viral recurrence [12].…”
Section: Discussionmentioning
confidence: 53%
“…It is unclear whether some of the deleterious effects of older donors are related to inability of the graft to mount an effective antiviral response or if there is some other explanation. Donor age at which this risk increases has been reported at various cutoffs: greater than 60 years [78], greater than 50 years [79], and as low as 40 years [76,[80][81][82][83]. These data beg the question of how organs from older donors should be allocated while balancing HCV status, Model for End-Stage Liver Disease (MELD), and wait times.…”
Section: Increasing Donor Agementioning
confidence: 92%
“…Furthermore, our multivariate analysis revealed that their use is associated with an increased incidence of recurrent hepatitis C (HCV). 14 …”
Section: Donor Agementioning
confidence: 97%